Comments on feed evaluation methods used in the project - Ribeiro J.M.C.R.; Moreira O.M.S.C. (Exploitation of Mediterranean roughage and by-products, 1998)
To begin with, the importance of the prediction of the nutritive value and intake of feeds for the ruminant animals is stressed. The prediction is mainly correlated to digestibility, NDF content and lignin content. Then the most important chemical methods, enzymatic methods and biological methods (in vitro, in vivo, in sacco) which can be used as predictors, are reviewed and commented. It is concluded that each method has its own validity and limitations in predicting the nutritive value of feeds. Among all the described methods, it is the author's opinion that the gas production technique was the most adequate in the present project.